Español - Garrido Huéscar, Elisa; Vandeweyer, lauren; García Mendivil, Laura; Hernández Bellido, Natalia; Pueyo, Esther; de Vos, Winnok H.; Ordovás, Laura (Jornada de Jóvenes Investigadores del I3A, 2023)
Molecular bases of cardiac aging still remain in the dark. Though hiPSC-CM are a usefull tool to study mechanisms, they present an immature phenotype. here, we present a maturation strategy and defind the progerin induction contitions for further aging analyisis in vitro.